Insult to Injury: Romantic Wartime and the Desecrated Corpse. Issue 3 (4th May 2019) - Clark, David L.
ABSTRACT: As a propaedeutic towards what I want eventually to call "a theory of the corpse, " my essay briefly considers images of Romantic remains—in particular, figures of desecrated, diminished, scorned, heaped, abandoned, unburied, forgotten, and otherwise ill-served and instrumentalized bodies of the war dead. Examining the figure of desecrated corpses in Jacques-Louis David, Sir Charles Bell, J. W. Turner, Jane Austen, and Felicia Hemans, I argue that the war dead pose unique challenges to historical knowledge and memory, and to the very concept of representation. The image of the marred corpse, I suggest, captures key features of the social and aesthetic derangements of Romantic war.